Carbohydrates - Vijay J. Naukudkar (New Innovations in Chemistry and Biochemistry Vol. 8, 2022)
Carbohydrates are naturally occurring organic compounds present in plants and animals. They are the source of energy for animals and plants. Every natural product which we eat contains carbohydrates in one or the other from. Compounds like glucose, fructose, cane-sugar, starch and cellulose which are widely distributed in plants are composed of carbon, hydrogen and oxygen and belong to the class of compounds called as carbohydrates. In this chapter importance of carbohydrates by considering plants and animals is explained. Explanation about classification and structure of carbohydrates is given. Ring structure of glucose and fructose is also mentioned. Concepts like Epimer, Mutarotation, Inversion, Reducing and non-reducing sugars are well defined. Reaction of glucose with acids, bases and oxidising reagents are also well explained.